If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100y + 15 = 75y + 17x Reorder the terms: 15 + 100y = 75y + 17x Reorder the terms: 15 + 100y = 17x + 75y Solving 15 + 100y = 17x + 75y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-75y' to each side of the equation. 15 + 100y + -75y = 17x + 75y + -75y Combine like terms: 100y + -75y = 25y 15 + 25y = 17x + 75y + -75y Combine like terms: 75y + -75y = 0 15 + 25y = 17x + 0 15 + 25y = 17x Add '-15' to each side of the equation. 15 + -15 + 25y = -15 + 17x Combine like terms: 15 + -15 = 0 0 + 25y = -15 + 17x 25y = -15 + 17x Divide each side by '25'. y = -0.6 + 0.68x Simplifying y = -0.6 + 0.68x
| x=-0.5+-2 | | (7x+14)+26+(180-(10+10x))=180 | | e^11x-1=(e^9)x | | 2d+2=5d-11 | | 2/3x=-5 | | 100y+15=75y+17 | | 4x+21=7y | | 2.5x+4.5=8 | | 7x^2+20x+3=0 | | Y=5/8b+10 | | 10+1/4y=3/4y-6 | | 54t-12t^2= | | 2n-6= | | 12y=-6(-0.5+2y)-3 | | -16x^2+4+3= | | 21.3n-8.1n+2.2n-28.5=1.6(n+5n)-5.3 | | 5(x+1)=-45+4x | | 4m-16=2m-2 | | 3/4x=6 | | -16x^2+k+3= | | 3x+5=104 | | 4k+11=6k+3-2k | | 2.5-7.5y=6 | | 8x+30=2x-6 | | f(x)=2x-3 | | 14y-8x=3 | | 4-8/3q=19 | | 3x+34=21x-74 | | r/42-6/7=6/7 | | 3/5k | | 4(n+69)-28=64 | | -2/3x=18 |